9z+12=9-3z

Simple and best practice solution for 9z+12=9-3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9z+12=9-3z equation:


9z+12=9-3z

We simplify the equation to the form, which is simple to understand
9z+12=9-3z

We move all terms containing z to the left and all other terms to the right.
+9z+3z=+9-12

We simplify left and right side of the equation.
+12z=-3

We divide both sides of the equation by 12 to get z.
z=-0.25

See similar equations:

| 1/2x=100 | | 2x-1/y=w+2/2z | | 2(m+3)+5m=-3 | | 390+215/35 | | (8+v)(3v+1)=0 | | 3/4(8x-2)=9 | | 390/35=215x | | 10+10x=x+19 | | 8x+3=-x+12 | | z-6/12=-5/12 | | 8x-3=3x-8 | | 6435+2457= | | x/5=3x/10+7 | | x/5=3x/7 | | 5-2/3a=7 | | 12w-7=53 | | 10(15-x)=0 | | 10(10x-100)=0 | | x^2+10x+25=-12 | | 11x-10=45 | | (3x^4+3x^3-6)-(5x^2-6x+3)= | | (x-8)=0 | | 71/2/25/8 | | 8(3x-30)=0 | | 7(2x-10)=0 | | 7m-10=11 | | (2/3)(180) | | 5(x+5)=0 | | (2/3)(270) | | (1/3)(270) | | 5x[7-(2x-1)]=3(x-5)+4(x+3) | | 9a^2+48a+32=0 |

Equations solver categories